Children of the dust - Lawrence, Louise, 1943- (New York : Harper & Row, 1985)
After a nuclear war devastates the earth, a small band of people struggles for survival in a new world where children are born with strange mutations.
Keywords: Nuclear warfare -- Fiction; Survival -- Fiction; Science fiction